Pengaruh mekanisme corporate governance terhadap kinerja keuangan dengan manajemen laba sebagai variabel intervening - Setiawan, Markus Hendra (Kajian Ilmiah Mahasiswa Manajemen, 2015)
This study had a purpose to determine effect of corporate governance mechanisms on financial performance through earnings management as intervening variable. This study took sample from manufacturing company listed on Indonesia Stock Exchange (IDX) during period 2009 to 2012. After do the selection process based on sampling criteria we got 38 companies that used in this research. In the first hypotheses we examined four variables of corporate governance mechanism towards earnings management. The results of data analysis showed that only managerial ownership variable had significant effect on earnings management actions, while institutional ownership, proportion of board independent, and the board size had no significant effect. On the second hypotheses we examined direct effect of earnings management toward financial performance. The results showed that earnings management had negative impact on financial performance but not significant. The third hypotheses examined effects of earnings management as intervening variable in the relationship between corporate governance mechanism and financial performance. The results showed that institutional ownership and board size had no significant effect on financial performance through earnings management. While managerial ownership and proportion of board independent had significant effect on financial performance through earnings management.